Types of Translation Strategies in Subtitling Java Heat Movie - Aldo . Pasaribu; Masitowarni . Siregar; Meisuri . Meisuri (LINGUISTIK TERAPAN, 2022)
Translation has always been the focus part of communication. A movie can convey information to the audience through pictures, dialogue and music. The picture is the visualization of the story on the screen, the dialogue is the conversation that occurs in the movie, and the music is the sound effect of the movie, which makes the story effective. The objective of this study is to explain the reason of utilizing translation strategies in Java Heat subtitling. The research deisgn used in the research is qualitative. There were eight types of translation strategies based on Baker’s theory in Java Heat movie namely translation by paraphrase using a related word (23.32%), followed by translation by omission (19.69%), translation by illustration (16.06 %), translation by a more general word (13.95%), translation by paraphrase using unrelated words (13.95%), translation by cultural substitution (8.79%), translation by using a loan word (3.44%), and translation by a more neutral/less expressive word (0.76%)”.